Business-to-business marketing communications : value and efficiency considerations in recessionary times /: value and efficiency considerations in recessionary times. ([2017]) - Rizomyliotis, Ioannis; Konstantoulaki, Kleopatra; Kostopoulos, Ioannis
No abstract available